Esfera pública burguesa e esfera pública proletária: as perspectivas de Habermas e de Negt e Kluge - Campato, Roger Fernandes (2007)
The goal of this thesis is to establish a comparison between the concepts of bourgeois public sphere and of proletarian public sphere developed, respectively, by Jürgen Habermas and by Oskar Negt and Alexander Kluge. In this sense, the study intends to demonstrate that, on contrary to Habermas eminently abstract perspective, the perspective suggested by Negt and Kluge is based on a non-deformed interpretation of marxist dialectics, allowing for the potential for emancipation present in the original critical theory.